2022
DOI: 10.3892/etm.2022.11611
|View full text |Cite
|
Sign up to set email alerts
|

Onodera's prognostic nutritional index: Comparison of its role in the severity and outcomes of patients with COVID‑19 during the periods of alpha, delta and omicron variant predominance

Abstract: Coronavirus disease 2019 (COVID-19) has posed a severe public health threat worldwide, affecting the function of multiple organs in affected individuals, in addition to respiratory function. Several strains of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been circulating worldwide since it first arose, with some of these having the ability to escape from natural or vaccine-mediated immunity. The Onodera's prognostic nutritional index (OPNI), which is derived from the peripheral lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…--------------------------------------------------------- -------------------------------------------------------- respiratory syndrome, with a COVID-19 mortality rate of up to 60% (27,28). Biomarkers such as NLR, CAR and albumin have all been reported as predictors of poor outcomes in patients with COVID-19 (29)(30)(31). To the best of our knowledge, the present study is the first to demonstrate the association of these specific inflammatory biomarkers with unfavourable outcomes among elderly patients receiving early remdesivir treatment, indicating the critical role of the nutritional and inflammatory state of these patients in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…--------------------------------------------------------- -------------------------------------------------------- respiratory syndrome, with a COVID-19 mortality rate of up to 60% (27,28). Biomarkers such as NLR, CAR and albumin have all been reported as predictors of poor outcomes in patients with COVID-19 (29)(30)(31). To the best of our knowledge, the present study is the first to demonstrate the association of these specific inflammatory biomarkers with unfavourable outcomes among elderly patients receiving early remdesivir treatment, indicating the critical role of the nutritional and inflammatory state of these patients in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the field of medical research has been confronted with immense challenges and has achieved significant advancements with regards to coronavirus disease 2019 (COVID-19) and obesity, both of which are conditions that are forming global health crises with varying degrees of coverage, attitudes and actions (1)(2)(3)(4). The interconnectedness of COVID-19 and obesity is addressed in the present article, which also highlights the complex nature of the interaction between these two prevalent problems in global health (1,2,(5)(6)(7)(8)(9)(10).…”
Section: The Interconnectedness Of Covid-19 and Obesitymentioning
confidence: 89%
“…Serum albumin levels have been linked to poor outcomes in patients with COVID-19. As a typical nutritional indicator, low albumin levels in patients with COVID-19 may be a marker of excessive consumption due to tissue damage and hypermetabolism ( 21 ). A recent study demonstrated that higher serum albumin levels are significantly associated with improved cognitive function and play a protective role in motor impairment and PD-related mortality ( 22 ).…”
Section: Discussionmentioning
confidence: 99%